Kerajaan Allah Menurut Lukas 17:20-37 dan Implikasinya Bagi Kehidupan di GKST Jemaat Baitani Wawopada - Tololiu, Naomi; Tamembuke, Aptun Alan (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This article aims to understand the meaning of the Kingdom of God according to Luke 17:20–37 and to examine its implications for the life of the congregation at GKST Baitani Wawopada. It employs a qualitative approach with two main methods: historical-critical hermeneutics to interpret the biblical text in depth, and descriptive field research to explore the congregation’s understanding and daily practices. The discussion reveals that the congregation perceives the Kingdom of God not merely as a future promise or worldly kingdom, but as a spiritual reality that has already come through Christ and is being lived out in their everyday lives. The Kingdom of God is expressed through acts of love, repentance, service, and obedience as tangible signs of God's presence among His people. The implications of this understanding are seen in their attitude of spiritual vigilance, active involvement in the church, and commitment to be a light in society. Thus, the Kingdom of God serves as a theological and ethical foundation for shaping the congregation's life in a meaningful and relevant way.